2019
DOI: 10.1016/j.jpowsour.2019.04.099
|View full text |Cite
|
Sign up to set email alerts
|

Optimized high performance thermoelectric generator with combined segmented and asymmetrical legs under pulsed heat input power

Abstract: Preventing a world energy crisis is one of the most important tasks of the 21st century due to the significant rate at which the world's energy demand is growing because of population growth and industrialization [1]. In addition, the excessive use of the depleting fossil fuels has caused global warming and environmental pollution thus, a viable solution is to promote the use of renewable and clean energy [2,3]. Renewable energy sources offer several advantages such as; sustainability, low pollution and econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 65 publications
(65 reference statements)
0
26
0
1
Order By: Relevance
“…Solar energy can be utilized commonly by converting it into electricity and heat [3]. Electricity can be generated directly by the photovoltaic (PV) from solar energy conversion therefore, the PV is one of the most attractive clean electricity generation technologies [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy can be utilized commonly by converting it into electricity and heat [3]. Electricity can be generated directly by the photovoltaic (PV) from solar energy conversion therefore, the PV is one of the most attractive clean electricity generation technologies [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that for the designed TE module, there is an optimal length ratio to the TE module to produce a maximum output, which depends not only on the material, but also on the geometrical structure. Therefore, except for improving the thermoelectric performance by enhancing the thermoelectric materials, thermoelectric performance can also be improved by improving the structure/geometry of thermoelectric components [11,36], such as the thermoelement length [86], the number of thermocouples [87], the ratio of thermocouple length to cross-sectional area [88,89], slenderness ratio (X = (A p /L p )/(A n /L n ) [86,[90][91][92] and the thermoelement with a special sectional area [93,94].…”
Section: Structure/geometrymentioning
confidence: 99%
“…Recent work showed that changing the shape of the legs (trapezoidal, rectangular, hexagonal, and cylindrical) and the alignment of the elements (inclination angle between the edge and the base), impacts temperature distribution, output power, efficiency conversion, and thermal stress distribution and also can improve TEG performance 9 11 . Shittu et al 12 showed that when making a severe geometric modification in one of the thermoelements, the output power can be increased; In the case of a rectangular thermoelement in conjunction with a trapezoidal thermoelement, the effect of asymmetry and segmentation is reflected in the increase of the output power by 117 in addition to reducing the thermal stress. However, it should be noted that the increase in output power is compared with a conventional TEG, so in this work, we analyze the geometric effect of asymmetry and segmentation with equivalent systems.…”
Section: Introductionmentioning
confidence: 99%